In vitro shoot induction from seed of Phaleria macrocarpa / Intan Syafeeqa Rosnani - Rosnani, Intan Syafeeqa (2019)
Phaleria macrocarpa known as God Crown's belong to Thymelaeaceae family posses several medicinal properties such as anti-angiogenic, anti-inflammatory and anti-proliferative. In this research, an attempt was made to initiate shoot induction and to differentiate rate of shoot induction from different concentration of plant growth regulators. The seeds were used as explants for culture initiation and germinated in vitro propagation of Phaleria macrocarpa. Shoot induction in MS media supplemented with three different concentration of each two different cytokinins were studied for twelve weeks. From the result 6-Benzylaminopurine (BAP) at 2.0 mg/L showed the most optimum concentration for shoot induction and showed highest number of leaves produced and shoot elongation. However, the number of shoot produced for the one explants highly showed in Kinetin (KIN) at concentration 1.0 mg/L.